EFEKTIVITAS PENERAPAN APLIKASI WEB 2.0 UNTUK MENINGKATKAN PEMBELAJARAN ORGANISASI DI PERPUSTAKAAN UNIVERSITAS PENDIDIKAN INDONESIA - Santi Santika; Pudji Muljono; Irman Hermadi (Jurnal Pustakawan Indonesia, 2017)
AbstractIndonesia University of Education (IUE) Library is required to continuously improve organizational learning so that the determinedquality policy is achieved. Organizational learning can work well if there is a media or device that can store, share and retrieve knowledgeof IUE library human resources that is currently stored on every individual. Web 2.0 technology is an application that can be used asa medium because it has the characteristics of read and write, and has the flexibility of the time of use. Web 2.0 technology is also analternative media that can be applied in IUE Library because 91% human resources of IUE Library using the Internet. Therefore, this study aims to find out Web 2.0 applications that can facilitate organizational learning in IUE Library and analyze the effectiveness of Web 2.0 application implementation developed in improving the learning process of the organization in IUE Library. The research method used is mixed method approach with the stages of research refers to the stages of development as well as stages of implementation in Web 2.0 Tools Implementation Model. Technique of effectiveness analysis using T test. The result of research show that blog and online forum can be used by IUE Library to facilitate organizational learning. The results of effectiveness test using T test with α = 0.05 stated that the application of Web 2.0 application in the form of blog and online forum effectively improve organizational learning in IUE Library and effectively improve individual learning level, group learning level, and organizational learning level.Keywords: organizational learning, web 2.0, blog, online forum